RETRACTED: Technological development of timber enterprises: equipment replacement mechanism - Medvedev Sergey; Zyryanov Mikhail; Gerasimova Marina; Shvetsova Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001